Factors Affecting e-leaners’ ability to learn English as a Foreign Language (EFL) online: A Literature Review - Al-Jubori, Shahlaa (lark, 2020)
AbstractThe decision recently taken by Iraqi universities to adopt e-learning as a teaching and learningmode has its own pedagogical effects. This is mainly represented by replacing the traditionalphysical setting by a new virtual one widely opening the door for new learning opportunities.Highly demanding as it is, e-learning is not without drawbacks. Highly demanding as it is, e-learning is not without its drawbacks, especially in the domain of English as a foreign language(EFL) teaching. EFL e-learners have different levels of proficiencies and weaker ones tend to beleft behind as they are more reserved and shier compared to their more eloquent peers. Hence,this paper attempts to identify factors that potentially affect (EFL) e-learners’ ability to learnonline and steps that could be taken to rectify issues related to weak and shy EFL e-learnersBased on the analysed literature four critical areas were identified and they are i) lack ofcognitive abilities; ii) lack of metacognitive abilities, readiness and motivation to learn languageonline; iii) lack of interaction with peers and teachers and iv) use of inappropriate or unsuitableEFL content.
Keywords: E-learning, E-learner, English as a Foreign language (EFL), low proficiency EFL e-learners